Capecitabine-induced oral mucosal hyperpigmentation associated with hand-foot syndrome - A literature review - Anna Danielly Almeida do Nascimento; Débora Maria Porto; Aurora Karla de Lacerda Vidal (Sociedade Brasileira de Dermatologia, 2023)
Abstract Background Capecitabine (Xeloda®) is a cytotoxic, antimetabolite chemotherapeutic agent. Its most common adverse events are diarrhea, hand-foot syndrome (HFS), hyperbilirubinemia, hyperpigmentation, fatigue, abdominal pain, and other gastrointestinal effects. HFS or palmar-plantar erythrodysesthesia (PPE) is an adverse reaction resulting from therapy with chemotherapeutic agents, classified into three degrees. Hyperpigmentation, as an adverse effect of capecitabine, can occur in different locations and with different patterns. The skin, nails and oral mucosal membrane can be affected. Objective The objective of this study was to report and discuss oral hyperpigmentation associated with HFS caused by the use of capecitabine, which is still poorly described in the literature. Methodology A literature review was carried out using the online databases PubMed, Scielo, BVS, Lilacs, Medline, BBO and Google Scholar, associating the descriptors "Capecitabine", "Pigmentation Disorders", "Oral mucosa", "Cancer" and "Hand-Foot Syndrome", which were related and used to exemplify, discuss and report the exposed clinical case. Results This case report corroborates the literature regarding the incidence in females and black skin persons like this patient who was affected by HFS when undergoing antineoplastic therapy with capecitabine and presented hyperpigmentation of the hands, feet and oral mucosa. On the oral mucosa, the hyperpigmented spots were diffuse, showing a blackish color and irregular edges. Their pathophysiology remains unknown. Study limitations Few articles citing capecitabine-associated pigmentation. Conclusions It is hoped that this study may contribute to the identification and correct diagnosis of hyperpigmentation in the oral cavity, as well as call attention to the adverse effects related to capecitabine.